The Waswanipi of James Bay - Feit, Harvey A. (Canadian Dimension, 1972)
Native communities in the James Bay region, despite their limited size, have maintained local control of decisions affecting the utilization of the basic resources on which they depend in spite of the appearance, from the point of view of white society, that decisions were increasingly being made in Ottawa and Quebec City. When they hunt animals outside the official nation-state regulations it is to maintain their community and family system of managing the resources in their region, and not the government's. I studied this at first hand in the Waswanipi region in the hunting seasons 1968-69 and 1969-70, several years after government regulation of beaver hunting had been abandoned in the area. Like the governments, the new hydro-electric and regional development corporations and their experts have not recognized that processes of land and resource management and control already exist in these communities. The absence of recognition is in part because there are no supra-ordinate authorities, over and above community-recognized family hunting leaders, who exercise effective resource and land management and control, there is no structure directly comparable to a nation-state system. Their failure is a threat to local autonomy.
© Harvey A. Feit, "Canadian Dimension," 1972, Vol. 8, No. 8.
Keywords: Self-governance; Hunting way of life; Conservation; Waswanipi; Hydro-electric project